TATA KELOLA DANA HAJI DI INDONESIA: PERSPEKTIF EFEKTIVITAS DAN TRANSPARANSI - Syaifur Rizal, M. Hasan (UIN Sunan Kalijaga, 2025)
This research aims to describe the management of Hajj funds in Indonesia by examining the effectiveness and transparency of their management. The research employed a literature review method, utilizing secondary data drawn from various studies that specifically discuss the management of Hajj funds in Indonesia. The research findings reveal that (1) the management of Hajj funds has become effective and efficient following the transition of fund management authority from the Ministry of Religious Affairs to the Hajj Financial Management Agency (BPKH), as demonstrated by continuous improvements in fund management since the establishment of the new institution, and (2) the management of Hajj funds has shown progress in transparency and accountability through the systems developed by BPKH, which enable access to relevant management data.